Management of hepatocellular adenoma: comparison of resection, embolization and observation. Issue 3 (9th October 2012) - Karkar, Ami M.; Tang, Laura H.; Kashikar, Nilesh D.; Gonen, Mithat; Solomon, Stephen B.; DeMatteo, Ronald P.; D' Angelica, Michael I.; Correa‐Gallego, Camilo; Jarnagin, William R.; Fong, Yuman; Getrajdman, George I.; Allen, Peter; et al.
Abstract: Introduction: Hepatocellular adenoma (HA) is an uncommon benign hepatic tumour with the potential for malignant change or spontaneous haemorrhage. Resection has been the recommended treatment, but outcomes with other approaches are ill defined. Methods: Demographic and outcomes data were retrospectively collected on patients diagnosed with HA at a tertiary hepatobiliary centre from 1992–2011 whom underwent resection, bland embolization or observation. Results: In total, 52 patients with 100 adenomas were divided into single HA ( n = 27), multiple HA ( n = 18), and adenomatosis ( n = 7) groups. Eighty‐seven per cent were female and 37% had a history of hormone use. Median sizes of resected, embolized and observed adenomas were 3.6 cm, 2.6 cm and 1.2 cm, respectively. Forty‐eight adenomas were resected as a result of suspicion of malignancy (39%) or large size (39%); 61% of these were solitary. Thirty‐seven were embolized for suspicion of malignancy (56%) or hsemorrhage (20%); 92% of these were multifocal. Two out of three resected adenomas with malignancy were ≥10 cm and recurred locally [4%, confidence interval (CI) 1–14%]. Ninety‐two per cent of the embolized adenomas were effectively treated; three persisted (8.1%, CI 2–22%). Most observed lesions did not change over time. Conclusions: While solitary adenomas are often resected, multifocal HAs are frequently embolized. Small adenomas can safely be observed. Given low recurrence rates, select HAs can be considered for embolization.